Factors Influencing Productivity of Smallholder Goat Farming in Rural Areas - Ahmad Zaki; Rozali Yahya; Minahasa Baubae (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Smallholder goat farming plays an important role in supporting rural livelihoods, improving household income, and strengthening food security in developing countries. However, the productivity of smallholder goat production systems remains relatively low due to various socioeconomic, technical, institutional, and technological constraints. This study aimed to analyze the factors influencing the productivity of smallholder goat farming in rural areas and to identify the most significant determinants affecting production performance. A quantitative survey approach was employed using primary data collected from 180 smallholder goat farmers through structured interviews. The study examined several explanatory variables, including farmers’ education level, farming experience, herd size, feeding management, animal health management, market access, institutional participation, and technology adoption. Data were analyzed using descriptive statistics and multiple linear regression analysis. The results revealed that all investigated variables had positive and significant effects on goat farming productivity. Feeding management emerged as the most influential factor, followed by herd size and technology adoption. Farmers who applied improved feeding practices, implemented effective animal health management, and utilized modern technologies achieved higher productivity levels than those relying on traditional production systems.